THE IMPORTANCE AND PARTICIPATION OF PEDAGOGICAL CREATIVITY (Conference Zone, 2022)
Beyond all recognition, the world we live in is changing and evolving. In any profession, it is necessary to work in accordance with the daily requirements. Teachers who work with the millennial age are also subject to a great deal of obligations and demands. A teacher should be aware of and responsive to the needs of today's students. This article explores how to foster students' creativity as well as the place of creativity in teaching.